Biomarcadores enzimáticos e ecotoxicidade por cobre em Eisenia andrei (Bouché 1972) - Ferreira, Talita (2015)
The indiscriminate use of agricultural supplies can cause soil pollution, affecting the flora, fauna and ecological relationships. Among these chemical compounds used in agriculture, there is the Bordeaux mixture. The intense use of this fungicide results in a considerable copper addition in the soil, may cause damage to exposed organisms. This study aimed to evaluate the toxicological effects of different copper doses, (0, 35, 70, 105, 140 e 175 mg.Kg-1) applied in soil, at earthworms Eisenia andrei biomass and reproduction, through ecotoxicological tests as well as the effects of exposure to antioxidant enzyme activity, by the enzymes catalase and glutathione S-transferase (GST and CAT), on neurotransmission biomarkers such as acetylcholinesterase (AChE) and cell membrane lipid peroxidation through the levels of malondialdehyde (MDA). The ecotoxicological results showed that the largest copper doses tested, (140 e 175 mg.Kg-1) were toxic, because the worms had a mean biomass reduction and cocoons. In the enzyme assessments, an increase in the glutathione-S-transferase activity was observed as the antioxidant defense mechanism. The significant MDA levels increase and the acetylcholinesterase activity inhibition, indicating the cell membrane lipid peroxidation occurrence and neurotransmission changes as a result of oxidative stress caused by the metal.